Mitochondrial adaptations to exercise do not require Bcl2‐mediated autophagy but occur with BNIP3/Parkin activation. Issue 3 (6th February 2020) - Ehrlicher, Sarah E.; Stierwalt, Harrison D.; Miller, Benjamin F.; Newsom, Sean A.; Robinson, Matthew M.
Abstract: Understanding the mechanisms regulating mitochondrial respiratory function and adaptations to metabolic challenges, such as exercise and high dietary fat, is necessary to promote skeletal muscle health and attenuate metabolic disease. Autophagy is a constitutively active degradation pathway that promotes mitochondrial turnover and transiently increases postexercise. Recent evidence indicates Bcl2 mediates exercise‐induced autophagy and skeletal muscle adaptions to training during high‐fat diet. We determined if improvements in mitochondrial respiration due to exercise training required Bcl2‐mediated autophagy using a transgenic mouse model of impaired inducible autophagy (Bcl2 AAA ). Mitochondrial adaptations to a treadmill exercise training protocol, in either low‐fat or high‐fat diet fed mice, did not require Bcl2‐mediated autophagy activation. Instead, training increased protein synthesis rates and basal autophagy in the Bcl2 AAA mice, while acute exercise activated BNIP3 and Parkin autophagy. High‐fat diet stimulated lipid‐specific mitochondrial adaptations. These data demonstrate increases in basal mitochondrial turnover, not transient activation with exercise, mediate adaptations to exercise and high‐fat diet.